Multidisciplinary Treatment of Hepatocellular Carcinoma - Vauthey, Jean-Nicolas.; Brouquet, Antoine; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
It is now widely accepted that multidisciplinary collaboration and multimodality treatment approaches are important in improving the survival of patients with hepatocellular carcinoma. In this comprehensive textbook, internationally renowned experts in the field present and discuss the various strategies employed in the treatment of the disease. Up-to-date information is provided on the indications for and outcome of a range of treatment options, including surgical resection, liver transplantation, radiofrequency ablation, transarterial chemoembolization, yttrium-90 transarterial radioembolization, and systemic therapy. In addition, important background information is included on biology, pathology, staging, and imaging. This book will be particularly helpful to all professionals and trainees worldwide who have an interest in the diagnosis and treatment of hepatocellular carcinoma.
Hepatocellular carcinoma (HC) biology -- Histopathology of HC -- Imaging of HC -- Methods to improve resectability of HC -- Surgical resection for small HC in cirrhosis: the Eastern experience -- Surgical resection for HC in non-cirrhoric liver: the Western experience -- Fibrolamellar HC -- Laparoscopic resection of HC -- Transplantation for HC: the European experience -- Transplantation for HC: the North American experience -- Living donor transplantation for HC -- Radiofrequency ablation for HC -- Transarterial chemoembolization of HC -- Yttrium 90 microspheres in the treatment of HC -- Targeted agents and systemic therapy for HC -- Multidisciplinary team and selection of appropriate treatment options for HC.
Keywords: Medicine; Oncology; Internal medicine; Clinical medicine; Medicine & Public Health; Oncology; Hepatology; Cancer Research; Internal Medicine